Burden of diarrheal diseases from biogas wastewater exposure among smallholder farmers in Ha Nam province, Vietnam - Phuc Pham Duc; Toan Luu-Quoc; Huong Nguyen-Mai; Tran Thi Tuyet Hanh; Tung Dinh-Xuan; Hang Tran-Minh; Hung Nguyen-Viet (Hanoi School of Public Health, 2016)
Livestock production has developed rapidly in Vietnam in recent years, particularly at the small-scale which account for 65% of the total livestock production. Biogas systems are commonly used to treat livestock waste, however, the health risks from biogas wastewater exposure at smallholder farms are not yet well understood. A quantitative microbial risk assessment approach was applied to estimate the burden of diarrheal diseases from biogas wastewater exposure among 451 smallholder farmers using biogas systems in Ha Nam province. A total of 150 biogas wastewater samples were collected and analysed for E. coli, Giardia, and Cryptosporidium. The study showed that farmers faced diarrheal disease risks due to exposure to biogas wastewater at different exposure scenarios. The calculated annual risk of diarrheal disease by E. coli ranked from 0.15 to 0.21; by Giardia ranked from 0.022 to 0.095; and by Cryptosporidium ranked from 0.006 to 0.015. The estimated diarrheal diseases burden from pathogens in all exposure scenarios largely exceeded the reference level of health outcome target of 10-6DALYs loss per person per year recommended by WHO. The results suggest the importance in reducing concentrations of pathogens in biogas wastewater before use in the fields as a means for mitigating public health impacts.